Computational Simulation and Developments Applied to Food Thermal Processing - Lemus-Mondaca, R (2011)
New challenges to improve food processing have created an incentive in the potential use of computeraided engineering for simulating thermal processes in foods as a viable technique to provide effective and efficient design solutions. Mathematical conjugated and nonconjugated models used along suitable numerical methods such as finite differences, finite elements, and finite volumes in predicting food freezing, dehydration, and sterilization are discussed in this review. The application of computational simulation should be used in combination with conventional techniques such as physical experiments and analytical solutions in order to enhance the knowledge of fluid mechanics, heat and mass transfer in foods. © 2011 Springer Science + Business Media, LLC.